O saneamento ambiental e a qualidade da água ofertada a população da cidade de Romaria-MG - Figueiredo, Vânia Santos (2021)
Brazil has increased the rates of sanitation services. However, it is still necessary to increase efforts and demand for management strategies and planning for universal access. According to data released in 2020 based on 2018 by the National Sanitation Information System, in Brazil, 16% of the population, approximately 35 million people, do not have access to treated water. In the state of Minas Gerais, 82.1% of the population has a drinking water supply. Regarding sanitary sewage, only 72.1% of the population receives sewage collection services, and only 39% of the mine sewage volume is treated. The city of Romaria, which is the focus of the research, is located in the state of Minas Gerais, in the upper course of the Bagagem river basin and is part of the Bauru aquifer, which is part of the Paranaíba river hydrographic network. The city is highlighted on the national scene for its religious festivals, but presents problems in environmental sanitation. The most serious of the investigated problems is the lack of water treatment and also in the treatment of sewage. Based on these conjectures, the objective of this thesis was to analyze the environmental sanitation conditions of the municipality of Romaria and the quality of the water offered to the population. The methodology used was an exploratory research. And how much the research approach is quali-quantitative. The approach method was anchored in the General Theory of the System. The procedures took place in several stages, such as bibliographic and documentary research, collections of water samples, several trips to the field that were essential to know the place and its nuances and, from there, propose improvement measures regarding the various problems found in the municipality. Finally, proposals were prepared that could be sent to the municipal manager, and to the public consortium, the Integrated Sustainable Development Region (RIDES) as a contribution to this thesis.